Diagnostic value of pulmonary acceleration time as a marker of pulmonary hypertension in children with congenital heart disease - Noviyani Leksomono; Indah Kartika Murni; Nadya Arafuri (Indonesian Pediatric Society, 2026)
Background Pulmonary acceleration time (PAT) and PAT to right ventricular ejection time (PAT/RVET) ratio are non-invasive echocardiography markers used to diagnose pulmonary hypertension (PH). Their diagnostic value in children with congenital heart disease (CHD) has not yet been studied in Indonesia. Objective To determine the diagnostic value of PAT and PAT/RVET ratio as markers of PH in children with CHD Methods This cross-sectional diagnostic study was conducted at Dr. Sardjito Hospital, Yogyakarta, from July to October 2025. Subjects were children aged 3 months to <18 years with left-to-right shunt CHD undergoing right heart catheterization. Echocardiographic PAT and RVET were measured <7 days before heart catheterization. Pulmonary hypertension was defined based on catheterization results [mean pulmonary artery pressure (mPAP) >20 mmHg]. Cut-off values for PAT and the PAT/RVET ratio were determined using receiver operating characteristic (ROC) curve analysis. Diagnostic performance was evaluated through sensitivity, specificity, positive and negative predictive values (PPV and NPV), and likelihood ratios. Subjects with severe right ventricular dysfunction were excluded. Results Of 106 subjects enrolled, 76 (71.7%) had PH. Various echocardiography-derived values (median PAT, mean indexed-PAT, mean RVET, and mean PAT/RVET ratio) were significantly decreased in the PH group compared to the non-PH group (P<0.001 for all). A PAT cut-off value of <120 ms demonstrated sensitivity of 86.3% (95%CI 76.3 to 93.2), specificity of 89.9% (95%CI 71.8 to 97.7), positive predictive value (PPV) of 95.5% (95%CI 87.8 to 98.4), negative predictive value (NPV) of 71.4% (95%CI 58.1 to 81.9), positive likelihood ratio (LR) 8.05 (95%CI 2.75 to 23.56), and negative LR 0.15 (95%CI 0.09 to 0.28). A PAT/RVET ratio of <0.47 showed sensitivity of 82.2% (95%CI 71.5 to 90.2), specificity of 67.9% (95%CI 47.7 to 84.1), PPV of 87.5% (95%CI 79.4 to 92.0), and NPV of 59.4% (95%CI 47.7 to 71.8), positive likelihood ratio (LR) 2.56 (95%CI 1.48 to 4.43), and negative LR 0.26 (95%CI 0.15 to 0.46). Conclusion Pulmonary acceleration time and PAT/RVET ratio are valid non-invasive markers with good diagnostic value for detecting pulmonary hypertension in children with left-to-right shunt CHD but PAT should not be used as a standalone tool.